SUSTAINABILITY THROUGH LOW COST TECHNIQUES IN INDIA (CHANNELIZING WORKS INFLUENCED BY ARCHITECTS) - Saxena, Manita; Sharma, Shruti (International Journal of Research -GRANTHAALAYAH, 2017)
“Sustainability through low cost housing” is a study based on some architects works of low-cost housing and there influences on architecture. Sustainable and low-cost is now a trend in architecture, there are many of the projects which are truly based on low cost techniques which was used by Sir Ar. Laurie baker and some architects still working on it. Study is to lighten up the latest techniques which they used in their projects, and his principles and selection of materials. Now a day, people think urban and a lavish life style, with affordable and eco logical friendly living. COSTFORD, is a bigger name in this field of low cost housing, where they are working on low-cost and providing lavish and wonderful places for their clients, and one more new organization are there “GOODEARTH” they are working on sustainability with their designing approaches and techniques.